Hubungan Pola Asuh Orang Tua dengan Kecanduan Gadget pada Anak Usia Sekolah Dasar - Aulia Kharin; Betie Febriana; Wahyu Endang Setyowati (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
Gadgets play a very important and helpful role in technology and communication. The progress in the use of gadgets is not only used by adults, one of which is elementary school age children. Gadgets themselves have positive and negative impacts, therefore parents need a parenting style to control and educate every child's activities. The aim of this research is to analyze the relationship between parenting styles and gadget addiction in elementary school-aged children. This type of research is quantitative research with a cross-sectional approach. The population of this study was 192 respondents. The sample size was 130 respondents who met the inclusion and exclusion criteria, then taken using simple random sampling technique. The instrument uses the PSDQ and smartphone addiction test. The independent variable is parenting style and the dependent variable is gadget addiction. Data were analyzed using the gamma correlation test. The research results obtained from the gamma test analysis with a significance value of α = 0.05 obtained a p value (value) = 0.031 <0.05, which means there is a relationship between parental parenting patterns and gadget addiction in elementary school age children. The conclusion is that parental parenting styles have a significant relationship to gadget addiction in elementary school-aged children.